A Publisher's Reader on the Verge of Modernity. - Nash, Andrew (Book History (Pennsylvania State University Press), 2003)
Profiles Frank Swinnerton, an author, publisher, broadcaster and reviewer in England, with focus on his contribution to publishing company Chatto & Windus as publisher's reader. Number of novels written; Role of Lee Warner, one of the senior members of the J. M. Dent firm, in bringing Swinnerton to Chatto & Windus; Privilege enjoyed by Swinnerton and Geoffrey Whitworth as editors under the management of Percy Spalding in 1876; Daily responsibilities of Swinnerton as a publisher's reader.